Prognostic significance of macrophage polarization in early stage oral squamous cell carcinomas - Weber, Manuel; Iliopoulos, Christos; Moebius, Patrick; Buettner-Herold, Maike; Amann, Kerstin Ute; Ries, Jutta; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Oral Oncology, 2016)
Polarization of tumor infiltrating macrophages is associated with the prognosis of solid malignancies and correlates with the occurrence of lymph node metastases in oral squamous cell carcinomas (oscc). Early stage (T1/T2, N0) oscc are characterized by a good prognosis and can be cured by surgery. The postoperative regime usually contains no adjuvant radio-/chemotherapy. The current pilot study was conducted to elucidate whether macrophage polarization in tumor resection specimens and diagnostic biopsies of early stage oscc is associated with tumor outcome.Patients with T1/T2, N0, and R0>5mm oscc without adjuvant therapy and 3-year follow-up after tumor resection were retrospectively selected. Tissue microarrays (TMA) containing diagnostic biopsies (n=17) and tumor resection specimens (n=17) were processed for immunohistochemistry in this pilot study to detect CD68-, CD11c-, CD163- and MRC1-positive macrophages. Samples were digitized, and the expression of macrophage markers was quantitatively analyzed.High infiltration of M2 polarized macrophages correlated with poor tumor outcome in early stage (T1/T2, N0) oscc. This correlation was observed in tumor resection specimens, but was also observed in diagnostic biopsies. M2 macrophage polarization in biopsies - but not in tumor resection samples - correlated with high scores in tumor grading.Macrophage polarization in early stage oscc is a potential prognostic marker for tumor outcome. The correlation of M2 polarized macrophages with tumor outcome can already be detected in the initial biopsies. Furthermore, M2 polarization of macrophages in biopsies is associated with an increased dedifferentiation.
EVALuna2:24408